Features of long term hospital stay patients in general surgery at Hospital Nacional Almanzor Aguinaga Asenjo - Díaz-Koo, Cristian Jesús (2020)
Introduction: Prolonged hospitalization constitutes a grave concern worldwide because its negative effects on the health system, raising their costs, generating a health service provision deficit, hospitalization and urgencies department saturation and as a result, greater adverse effects such as intrahospitalary diseases. Objective: Determine the characteristics of patients with prolonged hospital stay in the General Surgery service of the HNAAA. Results: It was found a mean of 15 days of hospitalization in long-stay patients. The characteristics most found in those patients were the delay in surgical procedures, abscense of a health system worker proximity (74%), age older than 65 years (58%) , being female (54%) and having a gastro intestinal neoplasm ( colon cancer :16%, ampuloma:10%, stomach cancer: 8%). Conclusion: The most common characteristics found were the delay in surgical procedure perform, delay in interconsult answer, the absence of an inside known doctor, administrative worker or cleaning service worker, age beyond 65 years, being female and having a gastro intestinal tract cancer.